PELATIHAN DAN PENDAMPINGAN PENYUSUNAN ARTIKEL ILMIAH BAGI PEMUDA GEREJA DI KOTA TOBELO - kour, femsy; Akerina, Febrina Olivia; Hibata, Yubelina (HIRONO : Jurnal Pengabdian Masyarakat, 2021)
Undergraduate education programs in a university require the completion of studies through research activities and set forth in the form of scientific works (thesis). Publication of scientific papers is one of the mandatory requirements in completing education in undergraduate programs. This training activity and assistance in writing scientific articles aims to help students compile scientific articles from scientific works. The activity lasted for 1 day which was divided into 2 sessions, namely the delivery of material and assistance in the preparation of scientific articles. the method used is participatory lectures and practice so that the material presented is easily absorbed optimally. After the activity took place there were 18 draft journals available or completed from 25 participants who took part in the training activities. This shows that the achievement of this activity is 72%.